Valuation of copyrights to audiovisual works: transparency practices of the copyright management organizations in the European Union - Kossecki, Paweł; Akin, Oguzhan (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The functioning of the audiovisual sector strongly depends on the use of copyrights and related rights. Problems with their clearing could harm the functioning of companies and might even lead to strong financial problems. The distribution of copyright-protected audiovisual works requires the licensing of rights by different rightsholders. Some of them are represented by Copyright Management Organizations (CMOs), which allow users to clear rights for many works without individual negotiations. Fees paid to CMOs for copyright-protected content constitute a significant part of operating costs for companies like TV stations, cable operators, VoD (Video on Demand) platforms. In case of intellectual properties for audiovisual works, CMOs make the valuation. They have been facing legal challenges due to subjective valuations as a result of being monopolies in the local market of the represented country and lack of transparency. Aim: This work explores the transparency of 21 CMOs in 4 EU countries due to their expected to be an integrated market status as the result of political and economic amalgamation. In addition to the adoption of The European Union Directive on collective management of copyright and multi-territorial licensing of rights, as part of the EU’s Digital Single Market project, this exploratory research, with comparative analysis of CMOs using the linear ordering methods, explains the necessity of an epagogic approach to creating correct institutions besides directives and laws, such as central observation, an ombudsman for conflict management, or an official body to employ these features in one structure to actively govern the market. Results: The conducted analysis allowed us to reflect on the importance of transparency and taxonomic mapping of the audiovisual market landscape will be the guideline to flatten the copyright valuation divergence in the EU and eventually will pave the way for fewer disputes and more innovations.